Achieving misalignment tolerance with hybrid topologies in electric vehicle wireless charging systems - Yiming Zhang; Zhongjin Huang; Hui Wang; Chao Liu; Xingkui Mao (Energy Reports, 2023)
With the rocketing progress of wireless power transfer (WPT) for electric vehicles (EVs), the issue of misalignment tolerance has become increasingly vital, a hybrid topology of the series–series (S–S) and inductor–capacitor–capacitor-parallel (LCC-P) is proposed in this paper to achieve misalignment tolerance. Both the S–S topology and the LCC-P topology have constant-current output, the difference is that the output power of S–S increases with the increasing misalignment, oppositely, the output power of LCC-P reduces with the increasing misalignment. A combination of these two topologies can enhance the anti-offset capability. The magnetic couplers utilize unipolar (Q) and bipolar (DD) coils as the two decoupled coils for power transfer. The mathematical model has been established and analyzed. The transfer efficiency and the output parameters’ expressions of current, voltage and power have been derived. The theoretical analysis has been verified in the simulation model of MATLAB/Simulink. The proposed hybrid topology has succeeded in achieving misalignment tolerance.